Pancasila Sebagai Ideologi Negara: Implementasi Nilai – Nilai dalam Kehidupan Nasional dan Internasional (Jurnal Begawan Hukum (JBH), 2024)
Pancasila is the foundation of the state and national ideology in the life of the nation and state. The function of Pancasila as an ideology, worldview, and state foundation must remain consistent. However, as an open ideology, Pancasila must be able to develop along with progress. The application of Pancasila ideology and Pancasila values can be applied in national and international life. This study produces findings from previous research related to the implementation of Pancasila as the state ideology. The research literature relies on written works, including published and unpublished research results, because this type of research is usually carried out without data searches. This research method uses a qualitative method. This data is collected from reference books, journals, and scientific articles. The main purpose of this journal is to improve the understanding and application of Pancasila values in national and international life. The results of the research are Pancasila as a state ideology which has deep values in it can be implemented in national and international life.